Dirac quasinormal modes of power-Maxwell charged black holes in Rastall gravity - Shao, Cai-Ying; Hu, Yu; Tan, Yu-Jie; Shao, Cheng-Gang; Lin, Kai; Qian, Wei-Liang [UNESP] (World Scientific Publ Co Pte Ltd, 2020)
In this paper, we study the quasinormal modes of the massless Dirac field for charged black holes in Rastall gravity. The spherically symmetric black hole solutions in question are characterized by the presence of a power-Maxwell field, surrounded by the quintessence fluid. The calculations are carried out by employing the WKB approximations up to the 13th-order, as well as the matrix method. The temporal evolution of the quasinormal modes is investigated by using the finite difference method. Through numerical simulations, the properties of the quasinormal frequencies are analyzed, including those for the extremal black holes. Among others, we explore the case of a second type of extremal black holes regarding the Nariai solution, where the cosmical and event horizon coincide. The results obtained by the WKB approaches are found to be mostly consistent with those by the matrix method. It is observed that the magnitudes of both real and imaginary parts of the quasinormal frequencies increase with increasing kappa, the spin-orbit quantum number. Also, the roles of the parameters Q and w, associated with the electric charge and the equation of state of the quintessence field, respectively, are investigated regarding their effects on the quasinormal frequencies. The magnitude of the electric charge is found to sensitively affect the time scale of the first stage of quasinormal oscillations, after which the temporal oscillations become stabilized. It is demonstrated that the black hole solutions for Rastall gravity in asymptotically flat spacetimes are equivalent to those in Einstein gravity, featured by different asymptotical spacetime properties. As one of its possible consequences, we also investigate the behavior of the late-time tails of quasinormal models in the present model. It is found that the asymptotical behavior of the late-time tails of quasinormal modes in Rastall theory is governed by the asymptotical properties of the spacetimes of their counterparts in Einstein gravity.
Keywords: Black hole; quasinormal modes; Dirac field; late-time tail; Rastall gravity